Phylogenomic Insights into Deep Phylogeny of Angiosperms Based on Broad Nuclear Gene Sampling - Yang, Lingxiao; Su, Danyan; Chang, Xin; Foster, Charles S.P.; Sun, Linhua; Huang, Chien-Hsun; Zhou, Xiaofan; Zeng, Liping; Ma, Hong; Zhong, Bojian (Plant communications, 2020)
Angiosperms (flowering plants) are the most diverse and species-rich group of plants. The vast majority (∼99.95%) of angiosperms form a clade called Mesangiospermae, which is subdivided into five major groups: eudicots, monocots, magnoliids, Chloranthales, and Ceratophyllales. The relationships among these Mesangiospermae groups have been the subject of long debate. In this study, we assembled a phylogenomic dataset of 1594 genes from 151 angiosperm taxa, including representatives of all five lineages, to investigate the phylogeny of major angiosperm lineages under both coalescent- and concatenation-based methods. We dissected the phylogenetic signal and found that more than half of the genes lack phylogenetic information for the backbone of angiosperm phylogeny. We further removed the genes with weak phylogenetic signal and showed that eudicots, Ceratophyllales, and Chloranthales form a clade, with magnoliids and monocots being the next successive sister lineages. Similar frequencies of gene tree conflict are suggestive of incomplete lineage sorting along the backbone of the angiosperm phylogeny. Our analyses suggest that a fully bifurcating species tree may not be the best way to represent the early radiation of angiosperms. Meanwhile, we inferred that the crown-group angiosperms originated approximately between 255.1 and 222.2 million years ago, and Mesangiospermae diversified into the five extant groups in a short time span (∼27 million years) at the Early to Late Jurassic. Angiosperms (flowering plants) are the most diverse and species-rich group of plants. The relationships among the early divergent lineages of angiosperms have been the subject of long debate. By assembling a phylogenomic dataset of 1594 genes from 151 angiosperm taxa, this study investigates the angiosperm phylogeny and reveals that a fully bifurcating species tree may not be the best way to represent the early radiation of angiosperms.